Methodological Development of a Combined Preparation for Micropaleontological and Sedimentological Studies of Samples From the Proterozoic Record - Denezine, Matheus; Adôrno, Rodrigo Rodrigues; Do Carmo, Dermeval Aparecido; Guimarães, Edi Mendes; Walde, Detlef Hans Gert; De Alvarenga, Carlos José Souza; Germs, Gerard; Antonietto, Lucas Silveira; Valdivia Rodríguez, Christian Gianfranco; Nunes Junior, Osvaldo De Oliveira (Frontiers in Earth Science, 2022)
Chemical, physical, and biological factors can influence individual microfossils' low recovery, becoming a barrier for biostratigraphic and paleoecological studies. Furthermore, low-cost projects with a reduced amount of sample collected, such as drill core sampling, need to optimize the preparation time and sample needed for different analyses. To overcome this challenge, it was combined the classical procedure of mineralized microfossil preparation, the palynological technique, and the study of clay mineralogy with the analyses of diagenetic alteration and the search for possible microfossils in thin sections. Three Proterozoic lithostratigraphic unities were selected to develop an integrated procedure for preparing samples for micropaleontologic and sedimentologic studies: the Paranoá Group, Mesoproterozoic, and the Bambuí Group, Ediacarian-Cambrian, Brazil, and Nama Group, Ediacaran-Cambrian, Namibia. Recovering individual microfossils from the Paranoá and Bambuí groups has been a challenge for paleontologists. Therefore, most micropaleontological studies have been done as a part of microbiofacies analyses in thin sections. All sediment fractions were studied in trial for the examination (and picking) of mineralized microfossils, even the finest ones. The microfossil picking was conducted using a stereomicroscope. Three species were recovered following this procedure: Vetronostocale aff V. amoenum Schopf & Blacic, 1971, Myxococcoides? sp. and Melanocyrillium? sp. Analyses in whole rock sample of residues from H2O and H2O2 procedures showed similar results when the clay fraction studied was obtained as part of micropaleontological preparation compared with the results from the standard clay minerals preparation method. The clay fraction diffractograms showed that the micropaleontological preparation with H2O and H2O2 caused an increase in the intensity of the quartz reflections compared to untreated samples. In addition, it is presented detailed protocols for organic-walled microfossils preparation and low concentrated acetic and formic acids attacks for mineralized microfossils extraction.